2010
DOI: 10.1590/s1519-69842010000400003
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved nitrogen in rivers: comparing pristine and impacted regions of Brazil

Abstract: Riverine nitrogen distribution is increasingly controlled by anthropogenic activities in their watersheds, regardless of spatial scale, climate, and geographical zone. Consequently, modelling efforts to predict the export of nitrogen from rivers worldwide have used attributes such as population density, land use, urbanization and sanitation. These models have greatly enhanced our understanding of the sources and fate of nitrogen added to terrestrial systems and transported to rivers and streams, especially for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
20

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 28 publications
0
17
0
20
Order By: Relevance
“…In the past, these criteria included only physicochemical parameters (Murray et al, 2001). Indeed, several studies have shown that urbanisation increases the concentration of some nutrients, such as nitrogen, ammonia, nitrate, and phosphorus, decrease the concentration of oxygen and is responsible for pH changes in rivers and streams (Hoare, 1984;Meybeck, 1998;Wernick et al, 1998;Martinelli et al, 2010;Cumar and Nagaraja, 2011;Padmalal et al, 2012). However, the analysis of the chemical and physical characteristics of an ecosystem becomes limited when the objective is the understanding of its complexity as the biological components should also be taken into account.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, these criteria included only physicochemical parameters (Murray et al, 2001). Indeed, several studies have shown that urbanisation increases the concentration of some nutrients, such as nitrogen, ammonia, nitrate, and phosphorus, decrease the concentration of oxygen and is responsible for pH changes in rivers and streams (Hoare, 1984;Meybeck, 1998;Wernick et al, 1998;Martinelli et al, 2010;Cumar and Nagaraja, 2011;Padmalal et al, 2012). However, the analysis of the chemical and physical characteristics of an ecosystem becomes limited when the objective is the understanding of its complexity as the biological components should also be taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…Since it has been shown that urbanisation is related to the incresase in nitrogen, ammonium and nitrate levels (Hoare, 1984;Meybeck, 1998;Wernick et al, 1998;Martinelli et al, 2010;Cumar and Nagaraja, 2011;Padmalal et al, 2012), one can hypothesise that it could influence the density and diversity of nitrifying and denitrifying microbes in impacted ecosystems. Considering the global nitrogen cycle, nitrification and denitrification are important steps.…”
Section: Introductionmentioning
confidence: 99%
“…Possui um potencial de aquecimento global, para um horizonte de tempo de 100 anos, 298 vezes superior ao do dióxido de carbono (CO 2 ) (IPCC, 2007), além de atuar indiretamente como um importante regulador dos níveis estratosféricos do ozônio (O 3 ) (CRUTZEN, 1979). Segundo Ravishankara et al (2009) et al, 2011;FILOSO et al, 2006;MARTINELLI et al, 2010 (FIDERJ, 1978;SCHUMM, 2003). A pluviosidade média anual varia de 1.500 mm (a jusante da bacia) a 2.800 mm (nas cabeceiras), com chuvas predominando no verão (FIDERJ, 1978;SCHUMM, 2003;SILVEIRA & RAMOS, 2007).…”
Section: Introductionunclassified
“…Sabe-se que a média mundial para exportação fluvial do N aportado em bacias hidrográficas é de 25% em relação ao N que entra no sistema (HOWARTH et al, 1996). Resultados obtidos por Martinelli et al (2010) Moreno et al (1996) em um estudo com milho irrigado com dois tratamentos, um que recebeu 500 kg N ha -1 e outro 150 kg N ha -1 , encontraram 30 e 25% de perdas fluviais no período chuvoso, respectivamente.…”
Section: Balanço Do Nitrogêniounclassified